Rintisan Desa Wisata Budaya melalui Pemberdayaan Kearifan Lokal dan Pemanfaatan Digital Marketing - Yusuf Yusuf; Gigih Ibnu Prayoga; Christianingrum Christianingrum (Journal on Education, 2023)
Dusun Air Abik, located in the Gunung Muda Village of the Belinyu District in Bangka Regency, has a potential natural landscape and local wisdom that is still being practiced, making it a primary value to be preserved. The indigenous tribe of Suku Lom or Urang Lom is led by a traditional leader who is a descendant of the original Urang Lom who does not have a belief system. The Mapur Customary Institution (LAM) has the task of preserving the traditions and beliefs of ancestors as well as preserving the customary forest. The PkM Dosen program aims to increase the creativity of the community in managing ecotourism potential by promoting local wisdom. The program includes workshops on the development of local wisdom-based tourism, branding and assistance in the use of social media and digital marketing for the development of medicinal plant education centers. The community faces both internal and external problems. Internal problems include stagnant social systems, belief systems regarding marriage (lineage), and threatened identity. External problems are focused on tenurial conflicts that have been going on for the past decade, namely the conflict over land disputes between palm oil plantation companies and Urang Lom, which threatens the preservation of local wisdom in the area. The community hopes that the community service program can provide a solution and have a positive impact on the process of Dusun Air Abik becoming a tourist village.